The Views on Terrorism in the Name of Islam Held by Islamic Religion Teachers in Spain - Navarro-Granados, María (Religions, 2020)
Violent radicalisation is currently one of the most pressing global problems. Accordingly, the intention of this paper is to discover the views on terrorism in the name of Islam held by Islamic religion teachers in Spain and to analyse the preventive socio-educational measures that they propose, employing a mixed methods approach with a questionnaire and semi-structured interviews. Most of the teachers point to a poor knowledge of Islam among the young, especially as regards to the concept of jihad, as the main reason behind this phenomenon. The second-generation immigrants among the teachers attach great importance to possible identity crises as a factor that makes the young more vulnerable to violent radicalisation. The most frequently mentioned social measure is fostering the integration of Muslims, thus creating a sense of belonging to their country of residence. They recommend preventive educational strategies that, far from focusing on detecting possible violent extremists, place the accent on teaching the fundamentals of the Islamic religion in order to provide young people with the tools that they need to challenge violent ideologies.